NOTARY AUTHORITY AS A CLASS II AUCTION OFFICIAL IN THE PERSPECTIVE OF THE NOTARY OFFICE ACT - Santika, Ida Bagus Agung Putra; Renaya, Nengah; Mahaputra, Kresna Yoga (NOTARIIL Jurnal Kenotariatan, 2023)
This study aims to determine the authority of a Notary as a Class II Auction Officer in the perspective of the Notary Position Act and to determine the legal consequences for a Notary who makes a minute of an auction who is not a Class II Auction Officer. This study employs normative legal research, utilizing the Legislation approach and Legal Concept Analysis (both analytical and conceptual approaches) as well as the Legislative Approach (statute-based approach). The results of this study are the harmonization of authority arrangements for Making Auction Minutes in terms of the Notary Position Act and auction regulations can be carried out using the lex specialist derogate legi generalist principle which is used in the Auction Rules as the basis for the authority to make Auction Minutes, which is contained in the Auction Officer, not the Notary. Although a Notary may be appointed as a Class II Auction Officer according to Article 7 of the Auction Instruction jo. PMK Class II Auction Officer, but the authority is given in the capacity of a Notary as a Class II Auction Officer who has been appointed by the Minister of Finance. Because a notary who has not been appointed as a Class II Auction Officer is not allowed to make a Minutes of Auction. The legal consequences for a Notary who makes auction minutes who is not a Class II Auction Officer will result in the degradation of the status of the auction minutes from an authentic deed to an auction minute which is only a private deed. The degradation of the status of the auction minutes from an authentic deed to a private deed will of course have other legal consequences, namely if the auction minutes are degraded into a private deed, then the auction minutes will no longer have perfect evidentiary power like an authentic deed.